2011
DOI: 10.1007/s10750-011-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of immobilized algicidal bacteria to control natural freshwater diatom blooms

Abstract: The purpose of this investigation was to assess the possible use of algicidal bacteria in conjunction with an immobilization technique for efficient termination of natural blooms of Stephanodiscus concomitant with minimization of adverse effects caused by a single application of bacteria. The performance of Pseudomonas fluorescens cells immobilized on cellulose sponges (CIS) was compared with that of freely suspended cells (FSC) of the organism at low water temperature (WT) of\10°C in co-cultures and natural m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Recently, novel PKS encoding genes were reported for a Pseudomonas strain isolated from the freshwater sponge Baikalospongia bacillifera [35] . However, in spite of their documented co-dominance [72] and biocontrol capabilities [73] , [74] in freshwater biomes, little is known about the genomic architecture and the spread and nature of secondary metabolite gene clusters of Pseudomonas species in these ecosystems. Collectively, our data suggest that the freshwater sponge E. fluviatilis is a promising source of underexplored Pseudomonas strains possessing a wide range of inhibitory activities whose underlying gene clusters and metabolites remain to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel PKS encoding genes were reported for a Pseudomonas strain isolated from the freshwater sponge Baikalospongia bacillifera [35] . However, in spite of their documented co-dominance [72] and biocontrol capabilities [73] , [74] in freshwater biomes, little is known about the genomic architecture and the spread and nature of secondary metabolite gene clusters of Pseudomonas species in these ecosystems. Collectively, our data suggest that the freshwater sponge E. fluviatilis is a promising source of underexplored Pseudomonas strains possessing a wide range of inhibitory activities whose underlying gene clusters and metabolites remain to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant genus group was Alteromonas. Many species of Alteromonas show an algicidal effect on various phytoplankton communities such as dinoflagellate, raphidophyte, and diatom, even working on phytoplankton species of freshwater [78][79][80][81][82][83].…”
Section: Microbial Food Web Structurementioning
confidence: 99%
“…Nakashima isolated a species of myxobacteria that lived in and could cause death to Cladophora glomerata (Nakashima et al 2006;Mu et al 2007;Chaiyaso et al 2011). Yoon carried out an algae-lysing test using different myxobacteria from a pool, and the results showed that 8 among 10 types of algae had been lysed (Kang et al 2012). M.J. Daft had also isolated from wastewater 9 myxobacteria that could lyse Anabaena azollae, Aphanizomenon flos-aquae, Microcystis aeruginosa, and some kinds of Oscillatoria (cited in Kang et al 2008;Kim et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is usually difficult to achieve this high concentration when the cells are employed in large bodies of water. Therefore, how to culture a hyperconcentrated cell culture is the key to dealing with algae bloom (Kang et al 2012). It is also pertinent to carry out detailed investigation on the effects, mechanism of action, and biosafety of any algae-lysing bacterium prior to its application in large bodies of water (Imamura et al 2000;Mayali and Doucette 2002;Nakashima et al 2006).…”
Section: Introductionmentioning
confidence: 99%